Hardening Baja AISI 1045 Menggunakan Gel Aloe Vera Sebagai Media Pendingin - Choiron, Moch. Agus; Darmadi, Djarot B.; Budiyanto, Eko (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2016)
Quenching is a cooling method of heat treatment for metal hardening. Quenching refers to the process of rapidly cooling metal parts from the austenitizing or solution treating temperature, typically from within the range of 815 to 970 Â°C for steel. The selection of a quenchant medium depends on the hardenability of the particular alloy, the section thickness and shape involved, and the cooling rates to achieve the desired microstructure. The liquid quenchants of oil is commonly used in industrial manufacture. But, oil is not environmental. The aim of this research research is to find new quenchant for change oil as quenchant to more environmental. Gel aloe vera is purposed for it. The material used in this study is AISI 1045 steel. Cooling curve and cooling rate is measured by finite element model, ANSYS APDL 14.5. True experimental is done to view microstructure and measure hardness of steel. Simulation result shown that gel aloe vera has almost similar cooling curve and cooling rate with oil. Microstructure result of steel for gel aloe vera as quenchant is martensite in surface, bainite in center, and pearlite in between surface and center. Hardness number of steel for gel aloe vera as quenchant is 189.63 HVN in surface, 182.566 HVN in center, and 162.866 HVN in between surface and center. By simulation and true experimental analisys concluded that gel aloe vera has opportunities to change oil as quenchant for hardening process.